Operations research applications of dichotomous search - Hassin, Refael; Sarid, Anna (European journal of operational research, 2018)
•This survey contains necessary background on dichotomous search.•It is the first survey on Operations Research applications of dichotomous search.•The focus is on models incorporating economic cost structure and constraints. An object is searched for in {1,⋯,N}. Queries for the object are sequentially conducted. A query at x reveals whether the object’s location is greater than x. The objective is to find the object within a minimal expected number of queries. This problem is called the “dichotomous search” problem and has many versions. This paper surveys dichotomous search problems with the emphasis on Operations Research applications.